Targeting CD38-dependent NAD+ metabolism to mitigate multiple organ fibrosis - Bo Shi; Wenxia Wang; Benjamin Korman; Li Kai; Qianqian Wang; Jun Wei; Swarna Bale; Roberta Goncalves Marangoni; Swati Bhattacharyya; Stephen Miller; Dan Xu; Mahzad Akbarpour; et al. (iScience, 2021)
Summary: The processes underlying synchronous multiple organ fibrosis in systemic sclerosis (SSc) remain poorly understood. Age-related pathologies are associated with organismal decline in nicotinamide adenine dinucleotide (NAD+) that is due to dysregulation of NAD+ homeostasis and involves the NADase CD38. We now show that CD38 is upregulated in patients with diffuse cutaneous SSc, and CD38 levels in the skin associate with molecular fibrosis signatures, as well as clinical fibrosis scores, while expression of key NAD+-synthesizing enzymes is unaltered. Boosting NAD+ via genetic or pharmacological CD38 targeting or NAD+ precursor supplementation protected mice from skin, lung, and peritoneal fibrosis. In mechanistic experiments, CD38 was found to reduce NAD+ levels and sirtuin activity to augment cellular fibrotic responses, while inhibiting CD38 had the opposite effect. Thus, we identify CD38 upregulation and resulting disrupted NAD+ homeostasis as a fundamental mechanism driving fibrosis in SSc, suggesting that CD38 might represent a novel therapeutic target.